The French Revolution Now; or, Carlyle's Eternal Return. Issue 1 (2022) - Allison, Mark
Abstract : This essay utilizes the publication of the first scholarly edition of The French Revolution: A History (1837) as an occasion to reassess this thoroughgoingly radical—and puzzlingly neglected—masterpiece. It explores how Thomas Carlyle's maverick conceptions of sympathy and affect, the relationship of the individual and the collective, and narrative itself underlie the audacious stylistic innovations that characterize this singular text. Moreover, this paper interprets Carlyle's history as a chronicle of inverted utopianism; that is, an apocalyptic manifestation of what is nevertheless a properly utopian longing for heaven on earth. Thus read, The French Revolution offers perspective on our own volatile times as well as a promise—or perhaps a warning—that the insurrectionary struggle for Liberty, Equality, and Fraternity is not over.